Multi Organ Dysfunction (MODS): A life-threatening aspect of traumatic brain injury - Akshita Garg; Nidhi Khatri; Bhanu Pratap Singh; Shweta Yadav; Arti Gupta (Indonesian Journal of Pharmacology and Therapy, 2025)
Traumatic Brain Injury (TBI) is not only a leading cause of neurological impairment but also a critical trigger for systemic complications. Among these, Multiple Organ Dysfunction Syndrome (MODS) represents one of the most severe and life-threatening outcomes. Following a primary brain insult, secondary pathophysiological cascades—such as neuroinflammation, oxidative stress, autonomic dysregulation, and the release of damage-associated molecular patterns (DAMPs)—initiate a systemic inflammatory response that affects peripheral organs including the lungs, liver, kidneys, and heart. This brain–body cross-talk results in multi-organ dysfunction, which significantly worsens prognosis and increases mortality. Understanding the mechanisms linking TBI to MODS is essential for early diagnosis, targeted therapeutic interventions, and improved patient survival. This review highlights the underlying pathophysiology, affected organ systems, and emerging management strategies to mitigate the systemic consequences of traumatic brain injury.